Peran Generasi Muda Sebagai Wujud Partisipasi Dan Kesadaran Masyarakat Dalam Pemilihan Umum 2024 - Maharani, Nabila; Mandira, I Made Chandra (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
The focus of this study is the participation of people in politics in the elections in the village of petiman petilan city of denpasar in 2024. It is important to investigate participation, as election success can be measured at the level of civic participation. Researchers use the research method of socialization. The study focuses on how people's political participation in the denpasar city legislature elections from 2024 to 2029. Friedmen and hechter feel that social institutions influence political participation. Research indicates that village heads, legislative candidate, PPS, and religious figures are social institutions that contribute to increased political participation of the community. Third, people's involvement and political perceptions are affected by the emotional closeness of the pileg and election candidates. Fourth, the rationality of society is central to political participation.